Contextualizing fatal police-resident encounters with a focus on Hispanic or Latin American Places: Does macro-level racial and ethnic composition distinguish resident fatalities by the police and police fatalities by residents?. (January 2021) - Zimmerman, Gregory M.; Fridel, Emma E.; Sheppard, Keller G.; Lawshe, Nathaniel L.
Abstract: Literature has documented racial and ethnic disparities in resident fatalities by the police and police fatalities by residents. Yet, there has been a lack of research on police-resident relationships within Hispanic communities. Additionally, research has rarely considered the relevance of social context for fatal police-resident encounters or examined resident and police fatalities concurrently. We use data on 7, 125 fatal police-resident encounters nested within 1, 739 agencies and 1, 506 U.S. census-designated places from 2000–2016 to examine whether macro-level racial and ethnic composition distinguishes resident fatalities and police fatalities. Results indicated that the odds of resident fatalities relative to police fatalities were significantly higher in majority Hispanic than majority white places. Racial disparities persisted in mixed-race places with at least 20% Hispanic residents. Furthermore, disparities were only observed in highly disadvantaged places, suggesting that racial and ethnic composition and structural disadvantage must be considered concomitantly to contextualize fatal police-resident encounters. Highlights: Resident (relative to police) fatalities were higher in majority Hispanic places. Racial disparities persisted in places with at least 20% Hispanic residents. Disparities were only observed in highly disadvantaged places. Racial/ethnic composition and disadvantage must be considered jointly.